Is occupational solar ultraviolet irradiation a relevant risk factor for basal cell carcinoma?: A systematic review and meta-analysis of the epidemiological literature - Bauer, Andrea; Diepgen, Thomas L.; Schmitt, Jochen Maximilian (British journal of dermatology, 2011)
Background The most important risk factor for basal cell carcinoma (BCC) is ultraviolet (UV) radiation. It is reasonable to assume that outdoor workers with a long history of work-related UV exposure are at increased risk of developing BCC. Objectives To analyse systematically the epidemiological literature concerning the evidence of an association between occupational UV exposure and BCC risk in outdoor workers. Methods Systematic literature review of cohort studies and case-control studies providing data on occupational UV exposure and BCC occurrence. PubMed (up to 28 January 2011) was searched, supplemented by hand searching and consultation of experts in the field. The association between occupational UV exposure and BCC risk is presented as odds ratios (ORs). A random-effects meta-analysis and sensitivity analysis including meta-regression on study-specific covariates were performed. Results Twenty-four relevant epidemiological studies (five cohort studies, 19 case-control studies) were identified. Twenty-three studies reported sufficient data to be included in the meta-analysis. The pooled OR for the association between outdoor work and BCC risk was 1·43 (95% confidence interval 1·23-1·66; P = 0·0001). Studies adjusting for sex (P < 0·0001) and individual nonoccupational UV exposure (P = 0·014) showed a significantly stronger association of occupational UV exposure and BCC risk. Meta-regression revealed a significant inverse relationship between occupational UV radiation exposure and BCC risk with latitude (P = 0·015). Conclusions Published epidemiological literature indicates that outdoor workers are at significantly increased risk for BCC. This finding is highly relevant for health policy to stimulate the implementation of effective prevention strategies.
Gesehen am 02.03.2022